How to Internalize Pollution Externalities Through 'Excess Burdening' Taxes - Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2002)
In the double dividend debate following Bovenberg and de Mooij (1994) the definition of tax efficiency dividend is implicitly based on the claim that by its very nature any corrective tax, and therefore any emission tax, imposes an excess burden, a claim that is also shared, e.g., by the advisory board of the German Ministry of Finance. We content that this view reflects inappropriate welfare economic reasoning, and offer an analytical concept for avoiding this deficiency. Our basic approach is to look at environmental externalities as synonymous with non-existence of markets and to take as the relevant point of reference for all taxes and subsidies an economy with a full set of markets. This common benchmark for all taxes is established by introducing fictitious markets to eliminate the market failure that gave rise to the pollution externality in the first place. Our main conclusion is that emission taxes replace (negative) producer prices on non-existing markets for pollutants generated in the process of production, and if the emission tax rates fall short of their Pigovian levels, if they are zero, in particular, those producer prices involve distortive and non-corrective! - emission subsidies. Internalization of environmental externalities means to set these virtual emission subsidies equal to zero. It is also shown that distortive taxes on 'dirty' consumer goods may turn out to be corrective, if no waste abatement technology is available.
Keywords: 330; Internalisierung externer Effekte; Umweltabgabe; Ökosteuer; Excess Burden; Theorie